Are free glucose and glucose-6-phosphate in milk indicators of specific physiological states in the cow?. (27th August 2014) - Larsen, T.; Moyes, K. M.
<x content-type="archive" xml:space="preserve">Abstract</x> A total of 3200 milk samples from Holstein and Jersey cows were analysed for free glucose and glucose-6-phosphate (G6P) by an enzymatic-fluorometric method that requires no pre-treatment. The cows were primiparous as well as multiparous, and samples were taken throughout the entire lactation period. In addition, lactose, protein, fat, citrate and β-hydroxybutyrate were determined and comparisons between these variables were made. Data were analysed using GLM model for the effect of parity, breed, time from last milking and stage of lactation on variations in parameters in milk. Pearson's correlations were generated between milk variables. P<0.05 was considered significant. Concentration of free glucose and G6P were on average 331 and 81 μM, respectively. Time from last milking (stay in the gland cistern) did not increase the concentration of these monosaccharides, indicating that they are not hydrolysis product from lactose post secretion, but rather reflecting the energy status of the mammary epithelial cells pre-secretion. Wide variation in range of these metabolites, that is, from 90 to 630 μM and 5 to 324 μM, for glucose and G6P, respectively, was observed. During the first 21 weeks in milk, free glucose increased whereas G6P decreased. Concentration of free glucose in milk is greater for primiparous than multiparous cows and greater for Holstein than Jersey cows. Concentration of G6P was not affected by parity or breed. The use of free glucose and G6P as indicators of physiological conditions and risk of disease is warranted for use as potential biomarkers for in-line surveillance systems on-farm.